Evaluasi Tata Kelola Teknologi Informasi Dengan Framework COBIT 5 Di Lembaga XYZ Cabang Denpasar - Dwiki Noviandra Kristanto; Alexander Setiawan; Andreas Handojo (Jurnal Infra, 2022)
XYZ Institute Denpasar Branch is a company engaged in the field of air traffic control. To carry out its business activities, until 2021, the company has 2 Main Branch Offices (KCU), 31 Branch Offices (KC), 31 Sub-Branch Offices (KCP), and 226 Aviation Navigation Service Units (UPNP). One of them is the Denpasar Branch of the XYZ Institute.Large companies have business processes with complexity and one of their main tasks is controlling spare parts for aviation telecommunications facilities and assisted by information technology. The company strives to control spare parts in detail, carefully and precisely to increase availability and reliability. The evaluation of information technology governance that has been implemented does not provide a definite guarantee for the company. Therefore, in the use of information technology, companies must focus on monitoring, maintenance, and management So in this research, the framework used is the COBIT 5 framework with the stages of Assessment Process Activities. The domain used in this study is EDM04 (Ensure Resource Optimization) which was obtained from the problems that occurred.